Heterosis performance in industrial and yield components of sweet corn - Assunção,Aracelle (2010)
Heterosis and its components were evaluated in a diallel crossing system of sweet corn. In the 38 treatments, eigth parents, 28 hybrids and two controls were used, arranged in a randomized block design with three replications.The diallel analysis followed the methodology of Gardner and Eberhart (1966). The following traits were evaluated: male and female flowering, plant and ear height, ear index (number of ears/number of plants), ºBrix, total ear weight, standard ear weight, industrial yield and total sugar content. There was genetic variability among genotypes, with significant differences except for the traits ear index, industrial yield and ºBrix.Heterosis was found for most traits. The mean heterosis of hybrids compared with the parents was positive for most traits. There was a contribution of additive and dominance effects.The contribution of dominant genes was greatest to flowering, plant and ear height and standard ear weight.